M Model Pengembangan Ekowisata Berkelanjutan Danau Kerinci Dan Danau Sipin, Provinsi Jambi: Integrasi Konservasi, Ekonomi Lokal, Dan Budaya: Model Pengembangan Ekowisata Berkelanjutan Danau Kerinci Dan Danau Sipin, Provinsi Jambi: Integrasi Konservasi, Ekonomi Lokal, Dan Budaya - Fariko, Andri; Efrina S, Liona; Ilfan, Freddy; Aswandi; Syaputra, M.Rialdi; Febriani, Yessi (Jurnal Khazanah Intelektual, 2026)
This study aims to formulate a sustainable ecotourism development model for Lake Kerinci and Lake Sipin, Jambi Province, which are currently facing the challenge of environmental degradation. Using qualitative and quantitative descriptive methods, the study identified potential natural and cultural tourism and analyzed existing environmental conditions. The results indicate that Lake Kerinci has natural ecotourism potential with a low level of degradation, while Lake Sipin requires rehabilitation intervention due to moderate pollution. The formulated development strategy includes cross-sector integration through a SWOT analysis, utilization zoning, and community empowerment through the Tourism Awareness Group (Pokdarwis).